Meaning of Education in the Bhagavad Gita - Ghimire, Janardan (Journal of Education and Research, 2013)
Our academia is familiar with the educational theories and thoughts developed in the West. However, we have no adequate information about our own historical and cultural thoughts in relation to education, despite their importance and comprehensiveness. In the Bhagavad Gita, I noticed that some of the basic components of educational philosophy are present. Among the various aspects of educational thoughts, this paper deals with the interpretation of the meaning of education that can be found in the Bhagavad Gita. Interpretation of a comprehensive meaning of education consisted within the Bhagavad Gita can contribute to inspire academicians to look behind the curtain of history for searching valuable knowledge. It can also provide some bases for comparative study of educational philosophy in the East and the West. From methodological perspective, this paper is a product of an Arts-based hermeneutical interpretation of a historical scripture that has established interesting links to cultural practice, personal experiences and feelings of the author. DOI: http://dx.doi.org/10.3126/jer.v3i0.7853 Journal of Education and Research March 2013, Vol. 3, No. 1, pp. 65-74